Efektivitas Prosedur Standar Operasi Pembaruan Perangkat Lunak Starlink Menggunakan Pengujian Wilcoxon Signed-Rank dan N-Gain - Azhari, Ozmar (Jurnal Teknologi Komputer dan Informasi, 2026)
In its operation, the Starlink service requires software updates to maintain the readiness and stability of satellite internet devices. However, procedural differences between Starlink V4 and Starlink FHP may create technical understanding challenges for users or technicians. This study aims to measure the effectiveness of the Standard Operating Procedure for Starlink software updates using the Wilcoxon Signed-Rank test and N-Gain. This study used a quantitative approach with a one-group pretest-posttest design involving 20 respondents. The research instrument consisted of 20 multiple-choice questions administered before and after respondents received the Standard Operating Procedure material. The material covered device activation, wireless network connection, device management application usage, connection status checking, update installation, and the use of a supporting wireless router for devices requiring additional configuration. The results showed that the average pre-test score increased from 49.25 to 79.00 in the post-test. The Wilcoxon Signed-Rank test obtained a significance value of 0.000 < 0.05, while the average N-Gain score was 0.59, categorized as moderate. Therefore, the Standard Operating Procedure was considered sufficiently effective in improving the technical understanding of Starlink software updates.Standard Operating Procedure